2023
DOI: 10.47655/dialog.v46i1.702
|View full text |Cite
|
Sign up to set email alerts
|

Peran Pesantren Tarekat Roudhoh Al-Hikam dalam Mengembangkan Tradisi Intelektual Islam dan Moderasi Beragama di Indonesia

Abstract: AbstrakPenelitian ini bertujuan untuk mengungkap peranan dan konsistensi Pesantren Tarekat terhadap pengembangan tradisi intelektual Islam dan moderasi beragama di Indonesia. Penelitian ini sekaligus menjawab dua problem besar umat Islam yang saat ini terjadi yakni surutnya tradisi intelektual dan mengikisnya kesadaran moderasi beragama, di mana dua hal tersebut telah lama terbangun. Penelitian ini menggunakan analisis Teori Manajemen Teror dengan studi kasus Pesantren Tarekat bernama Roudhoh Al-Hikam, yang be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The results of this research are supported by previous relevant research related to digital world training for students at Islamic boarding schools. This research found that the students had great enthusiasm and interest in utilizing technology to acquire future skills, and this training could help them improve their skills (Hidayatulloh et al, 2023;Paramita et al, 2023). This research also aligns with research on training using artificial intelligence (AI) in Islamic boarding schools.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The results of this research are supported by previous relevant research related to digital world training for students at Islamic boarding schools. This research found that the students had great enthusiasm and interest in utilizing technology to acquire future skills, and this training could help them improve their skills (Hidayatulloh et al, 2023;Paramita et al, 2023). This research also aligns with research on training using artificial intelligence (AI) in Islamic boarding schools.…”
Section: Discussionsupporting
confidence: 62%
“…Based on this problem, a solution is needed, including training and guidance regarding digital skills and the introduction of AI for students in Islamic boarding schools (Makridakis, 2018;Subowo et al, 2022). This training and guidance will likely provide provisions for students to improve their digital abilities or skills to be utilized in facing the realities of the field (Farisi, 2018;Hidayatulloh et al, 2023). This is supported by previous research stating that there was an increase in students' digital skills through training in Islamic boarding schools.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation